Religião e esfera pública na sociedade pós-secular: o diálogo entre religião e razão em Jürgen Habermas. - Silva, Emerson da (2018)
The present study aims to discuss the Habermasian understanding of the dialogue between religion and the public sphere in a post-secular society. The relation between religion and reason consists of the main nuclei of this interaction, observed in a concrete way in its theory of society and in the bases of the coexistence between religious and secularized individuals, socially related around a process of complementary learning. The focus of the investigation will be in the last publications of the philosopher that allude to a certain paradigm change with respect to his theories that deal with the subject. Religion and the public sphere are widely discussed themes within the author's theses, in keeping with the dynamics of his theory of communication. In his later works, an understanding of an intersection between these areas is advocated for a better establishment of human dignity and as a more concrete possibility of democratic relations in the liberal states. The symbolic goods of religious discourse, as well as the naturalistic worldviews of reality, when understood within their limits, and placed under a process of joint learning, can provide citizens with a better democratic interaction related to the themes of their interests present in the public sphere .